2016
DOI: 10.1186/s12870-016-0926-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of nuclear genes controlling chlorophyll synthesis in barley by RNA-seq

Abstract: BackgroundAlbinism in plants is characterized by lack of chlorophyll and results in photosynthesis impairment, abnormal plant development and premature death. These abnormalities are frequently encountered in interspecific crosses and tissue culture experiments. Analysis of albino mutant phenotypes with full or partial chlorophyll deficiency can shed light on genetic determinants and molecular mechanisms of albinism. Here we report analysis of RNA-seq transcription profiling of barley (Hordeum vulgare L.) near… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Various leaf color mutants have been described in barley ( Gálová et al, 2000 ) but only a few genes controlling leaf color have been well characterized ( Liu Z.L. et al, 2008 ; Qin et al, 2015 ; Shmakov et al, 2016 ). In this study, we showed that V-V-Y is a thermo-inducible chlorophyll-deficient mutant at the seeding and tillering stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various leaf color mutants have been described in barley ( Gálová et al, 2000 ) but only a few genes controlling leaf color have been well characterized ( Liu Z.L. et al, 2008 ; Qin et al, 2015 ; Shmakov et al, 2016 ). In this study, we showed that V-V-Y is a thermo-inducible chlorophyll-deficient mutant at the seeding and tillering stages.…”
Section: Discussionmentioning
confidence: 99%
“…et al, 2008 ). Recently, genes controlling chlorophyll synthesis have been explored by RNA-seq in barley Alm gene near-isogenic lines ( Shmakov et al, 2016 ). However, the genes responsible for chlorophyll biosynthesis and biodegradation and leaf color formation are largely unknown in barley.…”
Section: Introductionmentioning
confidence: 99%
“…The data was obtained from NCBI SRA database BioProjects PRJNA342150 (libraries of NIL i:BwAlm and isogenic line Bowman) and PRJNA399215 (libraries of NIL BLP and isogenic line Bowman). In PRJNA342150 experiment, transcriptomes of NIL i:BwAlm, based on isogenic line Bowman, plants lemma and line Bowman, taken as a control, plants lemma were compared (Shmakov et al, 2016). For each of the lines three biological replicates were taken.…”
Section: Methodsmentioning
confidence: 99%
“…Six short-read libraries were obtained by IonTorrent sequencing as described in Shmakov et al (2016). The libraries were filtered using PrinSeq-lite v 0.20.4 (Schmieder, Edwards, 2011).…”
Section: Bioinformatic Analysis: Libraries Preprocessingmentioning
confidence: 99%